2011
DOI: 10.1074/jbc.m110.206771
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Macrodomain Proteins as Novel O-Acetyl-ADP-ribose Deacetylases

Abstract: Sirtuins are a family of protein lysine deacetylases, which regulate gene silencing, metabolism, life span, and chromatin structure. Sirtuins utilize NAD ؉ to deacetylate proteins, yielding O-acetyl-ADP-ribose (OAADPr) as a reaction product. The macrodomain is a ubiquitous protein module known to bind ADP-ribose derivatives, which diverged through evolution to support many different protein functions and pathways. The observation that some sirtuins and macrodomains are physically linked as fusion proteins or g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
249
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 149 publications
(260 citation statements)
references
References 40 publications
10
249
1
Order By: Relevance
“…Tritium-labeled acetyl H3 peptide, H 2 N-KSTGGK( 3 H-acetyl)APRKQ-CONH 2 , was synthesized enzymatically from the 11-mer H3 peptide and purified as described previously (26). OAADPr, OPADPr, OBADPr, and O-3 Hacetyl-ADP-ribose ( 3 H-OAADPr) were synthesized enzymatically from ADPr and the acyl-peptides using yeast deacetylase HST2 and nicotinamidase from Salmonella enterica fused to maltose-binding protein (MBP-PncA) following procedures described previously (9,14). All other chemicals used were of the highest purity available commercially and were purchased from Sigma-Aldrich or Fisher Scientific.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Tritium-labeled acetyl H3 peptide, H 2 N-KSTGGK( 3 H-acetyl)APRKQ-CONH 2 , was synthesized enzymatically from the 11-mer H3 peptide and purified as described previously (26). OAADPr, OPADPr, OBADPr, and O-3 Hacetyl-ADP-ribose ( 3 H-OAADPr) were synthesized enzymatically from ADPr and the acyl-peptides using yeast deacetylase HST2 and nicotinamidase from Salmonella enterica fused to maltose-binding protein (MBP-PncA) following procedures described previously (9,14). All other chemicals used were of the highest purity available commercially and were purchased from Sigma-Aldrich or Fisher Scientific.…”
Section: Methodsmentioning
confidence: 99%
“…Protein Expression and Purification for Enzymatic AssaysExpression and purification of yeast HST2 (14,27) and nicotinamidase from S. enterica fused to maltose-binding protein (28) were performed as described previously (9). Expression and purification of the His-tagged C6orf130 protein for enzymatic studies was achieved by transforming E. coli BL21(DE3) cells with the pDEST17 plasmid containing the C6orf130 gene insert and induction of mid-log phase cells (A 600 ϭ 0.7) with 0.1 mM isopropyl-1-thio-␤-D-galactopyranoside at 23°C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…MACROD2 belongs to a family of genes containing a macro domain, an evolutionarily conserved protein motif (18), whose functional role until recently has been unclear. Studies have demonstrated that MACROD2 deacetylates O-acetyl-ADP ribose, a signaling molecule generated by the deacetylation of acetylated lysine residues in histones and other proteins (19). More recent work demonstrates that MACRO domain containing proteins are involved with mono-ADP ribosylation, and can regulate cell signaling pathways and modify proteins involved with gene transcription (20).…”
mentioning
confidence: 99%